OCCUPATION OF BUKHARA EMIRATE BY TSARIST RUSSIA - Nurmuhamedov Muradjon (American Journals, 2024)
In this article the author's research about the capture of the Bukhara Emirate by Tsarist Russia is unclear will also show the social situation of the Bukhara Emirate, the hardships they went through, and the achievement of independence.
Keywords: Bukhara Emirate, congress, BXSR, foundation lands.